(untitled) (African Journal of Biomedical Research, 2023)
The study examines the involvement of teenagers in e-waste activities on major landfills in Lagos state. Survey research design was adopted while both primary and secondary data were utilized for this study. A set of pre-tested structured questionnaire was administered to a purposively selected respondents (100) drawn from the three main landfills with 50 from Olusosun landfill, being the largest in size and 25 each from Abule–egba(Oke Odo) and Igando (Solous) respectively. Both descriptive and inferential (chi square) statistics were used to analyze the data at p≥0.05. The study revealed dominance (82%) of male across the landfills. more than two-thirds (69.0%) was Hausa. The roles of respondents on the job were self-employed (36.0%); apprenticeship (36.0%) while 26.0% works with their parents/guardians. Less than half (43.0%) of the respondents got paid through the sales of e-waste collected, Majority (44.0%) of the respondents received stippen from their bosses, parents/ guardian. There is statistically significant difference in physical health challenges faced by children workers on landfills (X2= 45.359). The government and other relevant local and international organizations should gear their efforts towards ending child labor in their state, and specifically in the country at large.